Administering Elections - Hale, Kathleen. author. aut Link
XXXIV, 211 p. 5 illus.
Keywords: Administering Elections provides a digest of contemporary American election administration using a systems perspective. The authors provide insight into the interconnected nature of all components of elections administration, and sheds like on the potential consequences of reforms that fail to account for this.